Effects of Ruta graveolens total and flavonoids extracts on rat blood glucose, cholesterol, triglycerides and urea comparing synthetic drugs - MITRA NOORI; MEHRANA JAFARI; HANIE AZIMI; MEHDI NODE-FARAHANI (Smujo International, 2019)
Noori M, Jafari M, Azimi H, Node-Farahani M. 2019. Effects of Ruta graveolens total and flavonoids extracts on rat blood glucose, cholesterol, triglycerides and urea comparing synthetic drugs. Nusantara Bioscience 11: 23-29. Rue (Ruta graveolens L.: Rutaceae) is a medicinal plant that is used to treat many diseases in America, Asia and Europe due to its pharmaceutical properties. So far more than 120 different phytochemicals such as flavonoids have been extracted and identified from the species, which make it valuable in traditional medicine and manufacturing of synthetic drugs. Due to its endemic and high potential pharmacological effects, this study examined the oral effect of each of its total, flavonoids and non-flavonoids extracts on reducing blood glucose, cholesterol, triglycerides and urea in STZ-diabetic rats comparing to control and Atorvastatin, Allopurinol, Metformin as synthetic drugs. Aerial part of the plant was collected from around Yazd, Iran and dried in shade, crushed and extracted in 70% ethanol in three steps. Total and flavonoid extracts were prepared after rotary evaporation, then were used for making required doses after calculation. The plant flavonoids were identified using two-dimensional, thin-layer chromatography and TLC Scanner3 methods. Atorvastatin, Allopurinol and Metformin were obtained and also appropriate doses were prepared. Thirty-six adult male Wistar rats were divided in 12 groups (n=3): control, synthetic drugs control, total and flavonoids control, STZ-diabetic control, diabetic treated with synthetic drugs, total and flavonoids extracts, then weighed. All rats were treated orally at a specific time for 2 weeks. Subsequently, the secondary rat weights were determined and blood donation was performed after anesthesia. Then, blood serum glucose, cholesterol, triglycerides and urea were determined by spectrophotometry using commercial enzymatic chlorometric assay kits. All data were analyzed using EXCEL and SPSS software. Results showed aerial part of R. graveolens contains flavones C and C-/O glycosides, flavonoid sulphates and had no aglycones. Apigenin, chrycin, isorhamnetin, kaempferol, myricetin, quercetin, rutin and vitexin were found in the species aerial part. This plant had 329/99 gr/kgDW of effective material and 257.7 g/kgDW of flavonoids. The lowest blood glucose levels were observed in treated Metformin and flavonoids control rats respectively. Diabetic rats treated with R. graveolens total extract had the lowest blood cholesterol, urea and glucose levels. The highest renal damage was observed in control diabetic rats and the least renal damage was observed in the STZ-diabetic rats treated with the plant total extract. These results indicate that R. graveolens extract and its rutin contained antihyperglycemia, antihyperlipidemia, insulinity and protective properties.